PERAN KEPADA SEKOLAH UNTUK MENINGKATKAN MUTU PENDIDIKAN BERBASIS ABSENSI ONLINE - Nurzula Yenti Basyaruddin (Jurnal Bahana Manajemen Pendidikan, 2019)
Attendance is one form of supervision or control of educators and employees carried out in the world of education. Attendance activities that have been running so far are still using a manual system, by recording the presence of education personnel and employees in the book or attendance paper. As a result, the possibility of errors or obstacles in making the recapitulation of attendance becomes large. Errors or obstacles that often arise include loss of paper or attendance list. One way to reduce the errors that occur is to create a system that can be used anywhere, using a database that will store attendance data so that the possibility of scattered data will be small